Ethical research in the German social sciences: Exploring the significance and challenges of institutionalized research ethics practices - Andrew Crawford; Laura Fichtner; Laura Gianna Guntrum; Stephanie Jänsch; Niklas Krösche; Eloïse Soulier; Clara-Auguste Süß (Research Ethics Review, 2025)
This article explores two key facets of institutionalized ethical review processes in Germany: (1) their importance in shaping ethical research and (2) their associated challenges, with a specific focus on their implications within the social sciences. Ethical considerations play a pivotal role in (social science) research, safeguarding, amongst others, the rights and well-being of participants and ensuring research integrity. Despite notable progress in promoting research ethics, German research institutions still need to significantly improve their ethics review processes. To address these challenges, this article emphasizes the need for expanding the current management of research ethics and implementing what we call “Institutionalized Research Ethics Practices’’ (IREPs), which include but go beyond the scope of common Institutional Review Boards (IRBs). Drawing on two workshops with researchers and IRB members, and a systematic review of existing IRBs in the German social sciences, we propose concrete recommendations for developing and enhancing IREPs, including a conducive environment, accessibility, fairness, and fostering expertise (CAFE). These enhancements aim to strengthen Germany’s research ethics infrastructure and promote responsible and ethical research practices in the social sciences.